Effectiveness of self-care monitoring on self-behavior of diabetes mellitus patients - Suciana, Fitri; Budi Syahputri, Rezyana; Winarti, Ambar; Pramono, Cahyo (Alma Ata University Press, 2024)
Background : Diabetes Mellitus is called the silent killer because this disease can affect all organs of the body and cause various kinds of complaints. Chronic hyperglicemia can affect the sufferes’s quality of life and cause rehospitalization. Decreased quality of life is caused emergence of hyperglicemia complications.. Controlling diabetes mellitus includes monitoring blood sugar levels, exercise or physical activity, diet, education and drug of diabetes mellitus. Diabetes mellitus is a metabolic disease that causes complications. The problem of complications is prevented by performing the 4 pillars of self-care while at home.Objectives : The purpose of this research is to determine the effectiveness of DM management on self-care. Methods : The research design in this study used a quantitative descriptive quasi-experimental method . The sampling technique used accidental sampling with a total of 30 respondents. Data analysis used the Wilcoxon test to determine pre and post results in each group and used the Mann Whitney test to determine the mean difference in the two groups. Inclusion criteria included respondents who were registered as prolanis members. The research instrument used a self-care monitoring sheet with the SDSCA (Summary of Diabetes Self-Care Activity) questionnaire with r table value 0.361 Results : The result is the Asymp.Sig value. (2 tailed) has a value of 0.001, so Ha is accepted, which means there is a difference in self-care ability between before being given DM management and after being given DM management. Based on the findings of researchers in this study, the value of Asymp.Sig. (2-tailed) value is 0.001, meaning that Ha is accepted. there is a difference between pretest and posttest in both the control and intervention groups. Conclusions : There is a difference in the average self care ability of diabetes mellitus patients using monitoring sheets. The conclusion is that the self-care management programme is effective on self-behavior.